Peran Air dan Sanitasi terhadap Pencegahan Infeksi Soil-Transmitted Helminths - Lustyafa Inassani Alifia (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2021)
Introduction: Soil-Transmitted Helminths (STH) infection is a tropical infectious disease that causes serious global problems. Based on WHO in 2018, there are more than 1.5 billion people or around 24% of the world’s population have been infected at least one of the species that causes STH infection. This STH infection can be prevented by optimizing the use of clean water, good sanitation, and adequate personal hygiene or WASH strategies (Water, Sanitation, and Hygiene). Purpose: The purpose of this article is to determine the role of water and sanitation in preventing infection of soil-transmitted helminths. Methods: This study was conducted with an article review that analyzes the role of water and sanitation in the prevention of STH infection. The article search was carried out by searching through the Google Scholar database by entering the keyword ‘soil-transmitted helminths, water, and sanitation”. This article was used 23 references based on references from reputable national and international journals to produce a comprehensive presentation. Results: Unclean water, unhygienic and unqualified sewage disposal that will eventually pollute the soil, wastewater disposal, and improper waste management are some of the risk factors where these STH species can continue their lifecycle and infect humans as the definitive host. Discussion: Inadequate sanitation can also contribute to an increased risk of STH infection, caused by an increase in the number of infective eggs from these species in the community, including in the soil. Conclusion: Poor sanitation increase the risk of the portal of entry to the host by swallowed by humans.